If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -4) = -3(x + -24) Reorder the terms: 9(-4 + x) = -3(x + -24) (-4 * 9 + x * 9) = -3(x + -24) (-36 + 9x) = -3(x + -24) Reorder the terms: -36 + 9x = -3(-24 + x) -36 + 9x = (-24 * -3 + x * -3) -36 + 9x = (72 + -3x) Solving -36 + 9x = 72 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -36 + 9x + 3x = 72 + -3x + 3x Combine like terms: 9x + 3x = 12x -36 + 12x = 72 + -3x + 3x Combine like terms: -3x + 3x = 0 -36 + 12x = 72 + 0 -36 + 12x = 72 Add '36' to each side of the equation. -36 + 36 + 12x = 72 + 36 Combine like terms: -36 + 36 = 0 0 + 12x = 72 + 36 12x = 72 + 36 Combine like terms: 72 + 36 = 108 12x = 108 Divide each side by '12'. x = 9 Simplifying x = 9
| -63-7x=7x+21 | | -7.4=u-16.4 | | 11-7x=63-21x | | 6x^2+10x-5= | | 1450=120(x) | | -115-7x=8x+20 | | 3x+13=-7-7x | | 5x+7=-45-8x | | 8+5(s-3t)= | | 3x+14=104-6x | | 5x+3=3x+20 | | 3x^2-2x+5=0 | | 3x+14=106-6x | | 25-7w=46 | | 3x^2-2x-5=0 | | 116-2x=6x-20 | | -6-5x=12-8x | | 50-6x=3x+18 | | -9r+3t-8s-r+12s+t-t+5s-11r= | | 79-2x=3x+14 | | d+241=648 | | 6-18x=4-17x | | 7(x-1)=5x-19 | | -56-2x=8-10x | | 3x+10=-56-8x | | 4(x+5)=4 | | 63-2x=2x+15 | | 0.4(3x+6)=1.5-(x+2) | | h+156=476 | | 5(x-8)=-30 | | 73-2x=9x+18 | | -6-2x=9-7x |